2022
DOI: 10.1097/hjh.0000000000003144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of obstructive sleep apnea in refractory hypertension

Abstract: Background:Refractory hypertension (RfHT) and obstructive sleep apnea (OSA) share common pathophysiological mechanisms and probably are intrinsically associated, but their prevalence, clinical profile, and polysomnography (PSG) pattern remain misunderstood.Objective:To describe OSA prevalence and PSG pattern of patients with RfHT in a large cohort of resistant hypertension (RHT).Methods:This is a cross-sectional study involving 418 RHT patients (30.9% male; mean age of 62.5 ± 9.9 years) who were submitted to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The prevalence of secondary hypertension, especially primary aldosteronism [728] and atherosclerotic renal artery stenosis (particularly in older patients or patients with CKD) can be as high as 10-20% of patients with resistant hypertension [716]. Search for OSA (by sleep history and specific tests) should not be omitted because of the frequent involvement of this condition in resistant hypertension, including night-time hypertension [729][730][731][732][733].…”
Section: Diagnostic Work-upmentioning
confidence: 99%
“…The prevalence of secondary hypertension, especially primary aldosteronism [728] and atherosclerotic renal artery stenosis (particularly in older patients or patients with CKD) can be as high as 10-20% of patients with resistant hypertension [716]. Search for OSA (by sleep history and specific tests) should not be omitted because of the frequent involvement of this condition in resistant hypertension, including night-time hypertension [729][730][731][732][733].…”
Section: Diagnostic Work-upmentioning
confidence: 99%
“…Ahmed et al 22 found that smoking and obesity were associated with increased risk for resistant hypertension in OSA patients. Smoking plays an important role in increasing blood pressure via activating sympathetic nerve system and interfering with the effects induced by certain antihypertensive drugs 27 . Neck circumference is commonly used to measure the degree of obesity in individuals, which has been demonstrated as independent risk factor for OSA with hypertension 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The association between OSA and drug refractory HTN is well established. There is a high prevalence (∼80%) of sleep apnoea patients with drug‐resistant or refractory HTN, and OSA has been considered a secondary cause of drug‐resistant HTN (Chedier et al., 2022; Logan et al., 2001; Pedrosa et al., 2011).…”
Section: Introduction: Sleep Apnoea Chronic Intermittent Hypoxia and ...mentioning
confidence: 99%